TEM investigation of metallic materials - an advanced technique in materials science and metallurgy - Jenko, Darja (Materiali in tehnologije, 2011)
The investigation of different metallic materials using high-resolution transmission electron microscopy (HRTEM) is presented. After thinning using argon ion-slicing thin foil specimens were prepared and further analyzed by various TEM analysing techniques at 200 kV, that make a powerful combination to resolve a large number of problems encountered in materials science and metallurgy. Some case studies of such problems are presented: influence of foaming agents in manufacturing processes of aluminium metal foams, removal of remaining oxides from the surface of duplex stainless steel (DSS), effect of low temperature ageing on properties of DSS, effect of heat treatment on the microstructure and properties of precipitate containing aluminium alloys.
Keywords: presevna elektronska mikroskopija; argon; silicij; dupleksna jekla; aluminijeve zlitine; aluminium alloy